Peran Herbal Medicine dalam Pencegahan Gangguan Neuro-Oftalmologis, Psikiatrik, dan Toksikologi Forensik : Suatu Kajian Sistematik - Ardizal Rahman; Hengky Ardian; Agung Wijayanto; Dwi Wijayanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Neuro-ophthalmological, psychiatric, and toxicological disorders caused by exposure to toxic substances represent a growing global health concern. Preventive approaches using herbal medicine have gained attention due to their relatively favorable safety profiles and broad pharmacological benefits. This study aims to investigate the effectiveness of herbal medicine in preventing disorders across these three domains, based on the latest scientific literature. The review was conducted following the PRISMA 2020 guidelines, with literature searches performed through PubMed, Scopus, and ScienceDirect using keyword combinations such as